Assessment of vehicle speeds and traffic safety along Commonwealth Avenue - Maata, Hazel E.
This study evaluates speeds along an urban arterial, specifically the Commonwealth Avenue. The primary objectives of this study are to measure the speeds of vehicles passing along Commonwealth Avenue, to perform statistical analysis on the data collected, and to assess road traffic safety and policies along Commonwealth Avenue. Spot speeds of vehicles were gathered using video surveys. These data were analyzed for each type of vehicle moving northbound or southbound at specific points along Commonwealth Avenue during different hours of the day. The analyzed data were compared to the data obtained by the International Road Assessment Programme (iRAP). The number of vehicles exceeding the 60-kph speed limit along the arterial was also determined. Findings include: (1) motorcycles have the highest speeds among the vehicle types; (2) the vehicles tend to have the highest speeds at the point near UP-Ayala Land TechnoHub; (3) the vehicles have relatively higher velocities along the southbound direction; (4) the afternoon period has the least velocity; and (5) motorcycles are more likely to exceed the 60-kph speed limit compared to other types of vehicle.